THE INFLUENCE OF HADITH-BASED COUNSELING ON STUDENT ACHIEVEMENT - Hafizh Akbar Widiyanto; Muhammad Ilyas (Yayasan Amanah Nur Aman, 2026)
Students' motivation and psychological condition play a crucial role in determining academic achievement in higher education, which is usually measured through course scores and Cumulative Achievement Index (GPA). One of the interventions that can be applied to support this psychological dimension is hadith-based counseling, which is a psychological guidance process that makes the hadiths of the Prophet Muhammad (peace and blessings of Allaah be upon him) the main foothold in giving direction to students. This study aims to examine how much contribution hadith-based counseling has to the achievement of UIN Sunan Gunung Djati Bandung students. Using a quantitative design with convenience sampling techniques, data was collected from 30 student respondents through a Likert scale questionnaire, then analyzed using simple linear regression analysis assisted by JASP software version 0.95.3. The results of the analysis showed that hadith-based counseling had a strong and significant positive relationship with student achievement, with a Pearson correlation coefficient (r) of 0.785. The determination coefficient (R²) of 0.617 indicates that the hadith-based counseling variable was able to explain 61.7% of the variance in the achievement of UIN Sunan Gunung Djati Bandung students, while 38.3% was influenced by other factors outside the scope of this study. .